Serum Cytokines Profile In Celiac Disease And Healthy Subjects - Abd, Atika Ahmed; Hamad, Dr. Wasan Sami; alhilli, Zina (Medical Science Journal for Advance Research, 2023)
Background and aims: .In This study measuring the levels of some cytokines in Najaf patients with CD and to compare with healthy subjects. Methods : This case control study was done to check the levels of markers in the serum of( 60) patients the celiac disease(CD) and who randomly recruited from different Hospital in Najaf Iraq during period between September 2022and January 2023 This was done using the ELISA method, and the results were compared with those of 40 healthy people who were the same age (18-50) and sex. The ages of the people in the case group ranged from (18 to 50) of celiac disease. Results: the mean level of Interleukin -2(IL-2) high significant different between patients and healthy groups and IFN-gamma no significant, Anti-tissue transglutaminase levels correlated and were show statistically significant with these IL-2 cytokines .and negative correlation between the amounts of marker in the serum and sex. Conclusion:IL-2 play role of pathology of celiac disease.